2017
DOI: 10.1016/j.amjcard.2017.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Left Ventricular End-Diastolic Volume–Mediated Declines in Ejection Fraction in Patients Receiving Potentially Cardiotoxic Cancer Treatment

Abstract: We sought to determine the frequency by which decreases in left ventricular (LV) end-diastolic volume (LVEDV) with and without increases in end-systolic volume (LVESV) influenced early cancer treatment-associated declines in left ventricular ejection fraction (LVEF) or LV mass. One hundred and twelve consecutively recruited individuals (aged 52 ± 14 years) with cancer underwent blinded cardiovascular magnetic resonance (CMR) measures of LV volumes, mass, and LVEF before and 3 months after initiating potentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…Decline in ejection fraction after cardiotoxic therapy may occur through increased end-systolic volumes related to myocellular dysfunction, but may also be caused by decreased end-diastolic volumes from cancer therapy–related nausea and volume depletion. 19 , 20 At follow-up, patients treated with candesartan had a decline in end-diastolic volumes but no change in end-systolic volumes, whereas participants who did not receive candesartan experienced increasing end-systolic volumes, but no significant change in end-diastolic volumes. It seems unlikely that the decline in end-diastolic volume is caused by volume depletion >1 year after end of cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Decline in ejection fraction after cardiotoxic therapy may occur through increased end-systolic volumes related to myocellular dysfunction, but may also be caused by decreased end-diastolic volumes from cancer therapy–related nausea and volume depletion. 19 , 20 At follow-up, patients treated with candesartan had a decline in end-diastolic volumes but no change in end-systolic volumes, whereas participants who did not receive candesartan experienced increasing end-systolic volumes, but no significant change in end-diastolic volumes. It seems unlikely that the decline in end-diastolic volume is caused by volume depletion >1 year after end of cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…93,94 Strain measurement is more sensitive to subtle damage of the myocardial ultrastructure that would otherwise be undetectable by echocardiography. 47,95,96 Early indicators of LV systolic dysfunction (LVSD) such as GLS may be useful for identifying patients at risk of anthracycline-based cardiotoxicity before the development of HF. 97 Studies have consistently shown significant GLS reductions in patients at cumulative doses of doxorubicin as low as 100e200 mg/m 2 , despite normal LVEF at the time of GLS assessment.…”
Section: Annals Of Oncologymentioning
confidence: 99%
“…Third, when assessing LVEF, one must consider whether a decline in LVEF occurs as a reduction in LVEDV or an increase in LVESV ( Figure 1 ). Meléndez et al ( 37 ) studied 120 patients with adult cancer 3 months after the administration of chemotherapy and observed that in those with LVEF declines >10%, nearly one-fifth experienced LVEF declines from isolated declines in LVEDV ( Figure 3 , Online Videos 1 , 2 , 3 , and 4 ). In a subsequent analysis on a subset of these same subjects, Jordan et al ( 38 ) observed that 16% of patients may experience deterioration in myocardial circumferential strain due to isolated declines in LVEDV ( 38 ).…”
Section: Dysfunctionmentioning
confidence: 99%